Moringa oleifera as a multifunctional feed additive: synergistic nutritional and immunomodulatory mechanisms in livestock production - Mohai Ud Din, Raza; Eman, Salwa; Zafar, Muhammad Hammad; Chong, Zhang; Saleh, Ahmed A.; Husien, Hosameldeen Mohamed; Wang, Mengzhi (Frontiers in Nutrition, 2025)
Investigating Moringa oleifera (M. oleifera)’ is potential as a livestock feed additive, this review explores its nutritional and phytochemical profiles and its mechanistic roles, specifically focusing on its immunomodulatory and antioxidant properties. M. oleifera is a rich source of diverse bioactive compounds, including polyphenols, alkaloids, terpenoids, flavonoids (e.g., quercetin, kaempferol), saponins, and tocopherols. These compounds exert significant immunomodulatory effects by modulating cytokine production and immune cell activity. Notably, Moringa-derived arabinogalactans (water-soluble polysaccharides comprising arabinose and galactose monomers) activate the gut-associated immune system through beneficial modulation of gut microbiota composition, increasing genera such as Muribaculaceae and Lactobacillus. The immunomodulatory activity is mediated via multiple pathways, including the promotion of anti-inflammatory cytokine secretion (e.g., IL-10) and the inhibition of pro-inflammatory enzymes [e.g., cyclooxygenase-2 (COX-2)]. Furthermore, M. oleifera exhibits potent antioxidant capabilities by enhancing endogenous defenses, neutralizing reactive oxygen species, and mitigating oxidative stress-induced tissue damage. These findings underscore M. oleifera is potential to enhance disease resistance and immune function in animals, advocating for its strategic incorporation into sustainable animal nutrition practices.